Anxiety in 3- to 7-year-old children with autism spectrum disorder seeking treatment for disruptive behavior. (February 2020) - Sukhodolsky, Denis G; Lecavalier, Luc; Johnson, Cynthia; Smith, Tristram; Swiezy, Naomi; Bearss, Karen; Kalvin, Carla B; Scahill, Lawrence
Anxiety is a common and impairing problem in children with autism spectrum disorder, but little is known about it in preschool children with autism spectrum disorder. This article reports on the characteristics of anxiety symptoms in young children with autism spectrum disorder using a parent-completed rating scale. One hundred and eighty children (age 3–7 years) participated in a clinical trial of parent training for disruptive behaviors. Anxiety was measured as part of pre-treatment subject characterization with 16 items from the Early Childhood Inventory, a parent-completed scale on child psychiatric symptoms. Parents also completed other measures of behavioral problems. Sixty-seven percent of children were rated by their parents as having two or more clinically significant symptoms of anxiety. There were no differences in the Early Childhood Inventory anxiety severity scores of children with IQ < 70 and those with ⩾70. Higher levels of anxiety were associated with severity of oppositional defiant behavior and social disability. Anxiety symptoms are common in preschoolers with autism spectrum disorder. These findings are consistent with earlier work in school-age children with autism spectrum disorder. There were no differences in anxiety between children with IQ below 70 and those with IQ of 70 and above. Social withdrawal and oppositional behavior were associated with anxiety in young children with autism spectrum disorder.